Recuperação mecânica de polímero termoplástico de baixa temperatura para uso em contextos hospitalares - Silva, Marion Silva da (2024)
In recent decades, there has been a huge tendency to reuse non-biodegradable and waste-forming solid waste to make new products. Currently, the recycling and employability of thermoplastic is well known. The low-temperature thermoplastic polymer presents itself as an alternative in the manufacture of various assistive technology devices, as it brings together excellent combinations of mechanical properties. Composed of cross-linked polycaprolactan (PCL) and polyurethane (PU), its application in the health sector is highlighted in two distinct sectors: in the manufacture of thermoplastic masks for fixation of patients undergoing head and neck treatment in Radiotherapy and Teletherapy, and in Occupational therapy. The latter, in the form of thermoplastic plates for making adaptable orthoses for limbs to better perform daily activities. Through mechanical recovery processes for thermoplastics and a collection network for this waste, involving public and private hospitals, a research project was established with the Master's Program in Professional and Technological Education (PPGEPT) aiming, through this technique, promote the reuse of discarded thermoplastic masks. In the normal cycle of use, masks used for their intended purposes are discarded as solid hospital waste. Based on a concept of Industrial Ecology and in line with the National Solid Waste Policy, studies and research into the reuse of this material are justified. The objective, in this way, is to contribute to minimizing the processes of environmental degradation, adding the advantage of reducing public spending and collaborating in the treatment of patients in the SUS network. The study is also justified by its contributions to the development of new technologies and innovation of the final product, proposing the reuse of solid hospital waste. This proposal is expected to reduce environmental and financial costs, adding advantages in the treatment of patients who would not have access to these treatment techniques. As a result, a viable technique is anticipated for the manufacture of a product from waste, with the purpose of use in hospital contexts and with potential for use in hospitals belonging to the Brazilian Hospital Services Company (Ebserh).